An Experimental Investigation into Nanofluids (Cuo-H2o &Cuo-Ethylene Glycol) Based Parabolic Solar Collector - Kandwal, Shailja (My University, 2015)
The concept of renewable energy gained importance after the degradation as well as the shortage of fossil fuels. Out of many renewable resources, solar energy has better prospect. Solar energy is available in bounty offering the benefits of being non- polluting, limitless and sustainability. It can be best used by converting it into other forms of energy as heat and electricity. The present study has been carried out to examine the performance of parabolic solar collector using CuO-water based nanofluids, CuO-ethylene glycol based nanofluids, water and ethylene glycol. A comparison has been made among all the four fluids at different concentrations (0.01%, 0.05% and 0.1%) and mass flow rates (160l/hr, 130l/hr and 100l/hr). Data has been collected from9:30 am to 2:30 pm in the months of April, May and June. CuO-water based nanofluids are found to have the maximum overall efficiency of 6.6% followed by CuO-ethylene glycol based nanofluids (5.73%), water (5.17%) and ethylene glycol (3.93%). These results are validated by the computational fluid dynamics (CFD) software using ANSYS 14.5. Solar load model has been used to calculate the solar heat flux. The input parameters used in the model are latitude and longitude of the location (Patiala), time and date of a particular day and orientation of the experimental setup. The experimental results are found to be in good agreement with the CFD results; within accuracy levels of ±5%.
ME, MED
Keywords: solar energy, collector, nanofluid, CFD; MED